Evaluation of a Repeat Offender Unit in Phoenix, Arizona, 1987-1989 - Petersilia, Joan ([Verlag nicht ermittelbar], 1992)
The purpose of this study was to evaluate the impact of a Repeat Offender Unit in Phoenix. Repeat Offender Programs are police-initiated procedures for patrolling and apprehending likely offenders in communities. These units typically rely on the cooperation of police and prosecutors who work together to identify, convict, and incarcerate individuals who are judged likely to commit crimes, especially serious crimes, at high rates. For this study, previous offenders were assigned either to a control or an experimental group. If an individual assigned to the experimental group was later arrested, the case received special attention by the Repeat Offender Program. Staff of the Repeat Offender Program worked closely with the county attorney's office to thoroughly document the case and to obtain victim and witness cooperation. If the individual was in the control group and was later arrested, no additional action was taken by the Program staff. Variables include assignment to the experimental or control group, jail status, probation and parole status, custody status, number of felony arrests, type of case, bond amount, number of counts against the individual, type of counts against the individual, number of prior convictions, arresting agency, case outcome, type of incarceration imposed, and length of incarceration imposed.